TO PLAY AND "ITSELF MOVE" IN EARLY CHILDHOOD EDUCATION, THE QUESTION OF PHYSICAL EDUCATION (Fiep Bulletin - online, 2011)
From the discussion of the theory and practice of teaching kindergarten this work further search in the areas of Early Childhood Education, Human Movement and Teacher understanding how to configure the impacts of new federal education guidelines. Investigating the complex and perceptions of child externalizing during their play and thus assess the role of the Professional Physical Education in the performance of early childhood education. The methodology is qualitative and social, that by comparison, evaluation and analysis of data collected through the literature review is organized to describe the research showing the reality of human development, especially the child. It can be stated as a conclusion that the performance of professional fitness trainer is crucial in kindergarten when one understands the world of the child must be respected at this time and when the pedagogical spaces provide environments emancipatory interaction, valuing it and move playing an essential element of early childhood education. However you can play and say "move it" as one of the essential elements of teaching in childhood, as this perspective is provided for free movement and learning from the play, so you can try their own ways of being.
Keywords: Early Childhood Education; be moving; and professional